Essay Writing Through Quantum Learning With Mind Mapping Strategy - Arini, Ni Wayan; Tristiantari, Ni Ketut Desia (JPI (Jurnal Pendidikan Indonesia), 2017)
This research was aimed atfinding out the improvement in Â essay writing skill in Scientific Writing course among the students of Elementary School Teacher Department of class GÂ  in semester VIÂ  in the academic yearÂ  2015/2016 after implementing QauntumÂ  LearningÂ  with Mind Mapping Strategy.Â  This study used classroom action research design that wasÂ  done gradually in multicyles. Each cycle consisted of planning, action, observation/evaluation and reflection. This study was done at Jurusan PGSD, FIP (Elementary School Teacher Department, Faculty of Education), Undiksha in the odd semester in the acacemic yearÂ  2015/2016 from April to November. The subjectsÂ  wereÂ  the students of class G in semester VI at Elementary School Teacher Department, Faculty of Education with the total number of 43 students.Â  The dataÂ  onÂ  the studentsâ€™Â  essay writing skill were obtainedÂ  by usingÂ  essay writing skill test. The result showed thatÂ  (1)Â  the mean score ofÂ  the studentsâ€™ essay writing skill in cycle I wasÂ  73.4, in cycle II it reachedÂ  81.5, (2) the number of studentsÂ  who belonged toÂ  â€œgoodâ€ and â€œvery goodâ€ categoriesÂ  in cycle I was only 58.5,Â  in cycle II it reached 88.4%, and (3) based onÂ  the computationi ofÂ  gain score it was found that the improvementÂ  inÂ  the studentsâ€™ writing skill wasÂ  0.333, falling intoÂ  â€œaverageâ€ category. It can be concluded thatÂ  the implementation ofÂ  Quantum Learning with Mind Mapping Strategy could improveÂ  essay writing skill of the sudents in class G in semester VIÂ  inÂ  Elementary SchoolÂ  TeacherÂ  Education Undiksha in the academic year 2015/2016. Â Â